2017
DOI: 10.1002/jemt.22859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different desensitizers and lasers on dentine tubules: An in‐vitro analysis

Abstract: The results of this study show that combined treatment methods were effective in the occlusion of dentinal tubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 35 publications
0
10
1
1
Order By: Relevance
“…Dentinal hypersensitivity’s incidence has been increasing due to many factors, and to this day no standard treatment has been available [30,31]. Conventional treatment was based on the use of desensitizing agents fixed on the dentinal surface, but the limitation of this treatment is that these agents do not last; therefore, the effectiveness is just temporary [32]. In this in vivo study, the decrease of DH was statistically significant and with long-term success.…”
Section: Discussionmentioning
confidence: 99%
“…Dentinal hypersensitivity’s incidence has been increasing due to many factors, and to this day no standard treatment has been available [30,31]. Conventional treatment was based on the use of desensitizing agents fixed on the dentinal surface, but the limitation of this treatment is that these agents do not last; therefore, the effectiveness is just temporary [32]. In this in vivo study, the decrease of DH was statistically significant and with long-term success.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all three laser types showed equal efficacy. However, it should be noted that the diode laser used in our study had a 980 nm wavelength, which was different from the wavelength of the diode laser used by Saluja et al 24 Öncü et al 25 evaluated the efficacy of different desensitizing agents and lasers for the obstruction of dentinal tubules. They concluded that the Er:YAG laser combined with Gluma had the highest efficacy for tubular obstruction, which was different from our results.…”
Section: Discussionmentioning
confidence: 93%
“…A new approach consists of combining the laser, the fluoride varnish, and/or the use of a desensitizing agent. The advantages of such an approach are justified by combining multiple effects, which can lead to more meaningful results , …”
Section: Discussionmentioning
confidence: 99%